Aspects of the community structure and reproductive ecology of the common sea-urchin Parechinus angulosus Leske around the Cape Peninsula, South Africa - Fricke, A H (Department of Oceanography, 2019)
The geographic distribution of Parechinus angulosus according to present records extends from Umhlali (Zululand) to Luderitz Bay (Day, 1974). The urchins are therefore adapted to a fairly wide range of temperatures. Maximum fluctuations probably occur along the stretches of coastline affected by upwelling, the south-west and west coasts, with differentials of twelve degrees Centigrade and more. Furthermore, these fluctuations may take place within a matter of a few hours or even less, i.e. almost capriciously like temperature changes encountered on land but, unlike, the latter, by virtue of movement of different water masses, rather than cooling rate. The importance of temperature as a regulator of reproductive cycles in marine organisms, specifically invertebrates, is discussed in Giese and Pearse's (1974) detailed review on the subject. A local study by Newman (1969) considers the effect of temperature on the spawning behaviour of abalone (Hal,iotis midae). This study was commenced in the light of this information and subjective preliminary observations underwater, which revealed striking density and relative size differences between urchins on the Atlantic side of the Peninsula and in the warmer False Bay. A detailed in situ record of sea temperatures at two study sites, Robbeneiland and Millers Point was obtained by installing temperature measuring devices. This monitoring covered a period of one year, while coupled with monthly collections of urchins in the mature size range. The variations of male and female gonad indices were found to be essentially in agreement, though lagging behind sea temperature changes.